Litteraturen rykker nordpå: Om Grønland i 10’ernes danske litteratur - Dybdal, Emilie (Aarhus Universitetsforlag, 2021)
This article investigates Greenland as a setting in new Danish prose. I make the case that Danish literature about Greenland is a significant trend in the 2010s, and that the books can be divided into three dimensions: past, present and future. Focusing on space and place, I exemplify this division through short analyses of the novels Rød mand/Sort mand (2018) by Kim Leine, Godhavn (2014) by Iben Mondrup and Korsveje i Nord (2015) by Bjarne Ljungdahl, which are set in the past, present and future, respectively.